Instruction matters to the development of phoneme awareness and its relationship to akshara knowledge and word reading: evidence from Sinhala - Wijaythilake, M; Parrila, R; Inoue, T; Nag, S (Taylor and Francis, 2018)
We examined whether global instruction of complex akshara and explicit phoneme-level instruction of akshara impact the development of phoneme awareness and its association with akshara knowledge and word reading accuracy. The participants were 100 Sinhala-speaking children from Grades 4 and 5 in Sri Lanka. Phoneme awareness showed stronger growth and a significant relationship with word reading accuracy and akshara knowledge only after children received explicit phoneme-level instruction in akshara construction. Both word reading accuracy and akshara knowledge predicted phoneme awareness, but the opposite was not true. The results suggest that phoneme awareness in Sinhala is sensitive to the method of reading instruction, and contrary to the studies in alphabetic languages, it does not have a bidirectional relationship with reading.